KEMAMPUAN LITERASI MATEMATIS DAN EFIKASI DIRI SISWA MADRASAH TSANAWIYAH - Ranti, Mayang Gadih (Koordinat Jurnal MIPA, 2023)
The purpose of this study was to describe the mathematical literacy skills and self-efficacy of Madrasah Tsanawiyah students and examine the relationship between the two. The research method used is quantitative descriptive and is a correlational study. The research was conducted on 105 class VII students of MTsN 6 Banjar by using a mathematical literacy ability test and a self-efficacy questionnaire. The results showed that students' mathematical literacy skills had an average value of 61.03 and were in the good category, while self-efficacy had an average value of 61.21 and were in the high category, and through the product moment correlation test it was found that there was a positive relationship between students' ability mathematical literacy and student self-efficacy